Importance of an International Registry for and Collaborative Research on Esophageal Atresia - Gottrand, Frédéric; Ley, Delphine; Michaud, Laurent; Sfeir, Rony (Frontiers in Pediatrics, 2017)
Esophageal atresia (EA) is a rare congenital defect. Data on EA prevalence, management, and long-term outcome are lacking because the available data come from small retrospective series from tertiary referral centers. An international multicenter registry would provide strong epidemiological data from large population-based cohorts on EA prevalence and incidence, treatment, long-term morbidity, and prognosis and would thus provide accurate data for evaluation of the current guidelines for EA management. The future challenge of the new international network on EA, which was created in 2013, is to promote the creation of a collaborative database and further studies.